Serious Workplace Violence Against Healthcare Providers in China Between 2004 and 2018 - Ma, Jing; Chen, Xi; Zheng, Qiongjuan; Zhang, Yun; Ming, Zhi; Wang, Dongxin; Wu, Hua; Ye, Haisen; Zhou, Xiaoxuan; Xu, Yunxuan; Li, Renjiao; Sheng, Xia; et al. (Frontiers in Public Health, 2021)
Introduction: Workplace violence (WPV) against healthcare providers has severe consequences and is underreported worldwide. The aim of this study was to present the features, causes, and outcomes of serious WPV against healthcare providers in China. Method: We searched for serious WPV events reported online and analyzed information about time, location, people, methods, motivations, and outcomes related to the incident. Result: Serious WPV reported online in China (n = 379) were mainly physical (97%) and often involved the use of weapons (34.5%). Doctors were victims in most instances (81.1%). Serious WPV mostly happened in cities (90.2%), teaching hospitals (87.4%), and tertiary hospitals (67.9%) and frequently in Emergency Department (ED), Obstetrics and Gynecology Department (OB-GYN), and pediatric departments; it was most prevalent in the months of June, May, and February. Rates of serious WPV increased dramatically in 2014 and decreased after 2015, with death (12.8%), severe injury (6%), and hospitalization (24.2%) being the major outcomes. A law protecting healthcare providers implemented in 2015 may have helped curb the violence. Conclusion: Serious WPV in China may stem from poor patient–doctor relationships, overly stressed health providers in highly demanding hospitals, poorly educated/informed patients, insufficient legal protection, and poor communication. Furthering knowledge about WPV and working toward curtailing its presence in healthcare settings are crucial to increasing the safety and well-being of healthcare workers.